Decoding MSME Entrepreneurship: A Study from Bogor, Indonesia: Menguraikan Kewirausahaan UMKM: Sebuah Studi dari Bogor, Indonesia - Palahudin; ayu pramestidewi, Chandra; Awa; Yulianingsih (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2024)
This research explores the entrepreneurial behavior characteristics of MSMEs in Nagrak Village, Bogor, aiming to provide empirical insights that guide MSME actors in enhancing their business success. Employing a survey method with a descriptive analysis approach, data was collected through observation, interviews, and questionnaires from 27 MSME entrepreneurs. Results indicate that MSMEs in Nagrak exhibit generally strong entrepreneurial behavior, with respondents showing high levels of entrepreneurial knowledge, positive mental attitudes towards entrepreneurship, and proficient entrepreneurial skills. These findings underscore the importance of nurturing knowledge, attitude, and skills in entrepreneurship to foster successful MSME businesses. The study offers valuable input for MSME entrepreneurs in Nagrak, suggesting areas of focus to further improve their entrepreneurial endeavors and achieve business success.